A Case Presentation on Rheumatic Heart Disease with Mitral Regurgitation - A., Jayasudha; B., Sreerenjini; P., Kaveri; P., Anitha (Journal of Health and Allied Sciences NU, 2019)
During any pregnancy there is an increase in blood volume of 30 to 50% resulting in increased pressure on the heart valves. For women with rheumatic heart disease this increased pressure presents increased maternal and/or fetal risks. Counseling of women with rheumatic heart disease gives appropriate surveillance of maternal and fetal well-being, as well as planning and documentation of the management of elective and emergency delivery. The care of pregnant women with rheumatic heart disease thus requires a multidisciplinary approach, involving obstetricians, cardiologists, and anesthetists. However, many women with rheumatic heart disease have healthy pregnancies and healthy babies with the right medical care.